"It's not an illness, it's just bad luck": The impact of anaphylaxis on quality of life in adults. Issue 7 (27th June 2019) - Knibb, Rebecca C.; Huissoon, Aarnoud P.; Baretto, Richard; Ekbote, Anjali; Onyango‐Odera, Shamim; Screti, Cassandra; Newman, Kristina L.; Krishna, Mamidipudi T.
Abstract: Background: An increasing number of adults are being diagnosed with anaphylaxis, but its impact on health‐related quality of life (HRQol) is not known. Objective: The aim of this study was to explore the impact of anaphylaxis on HRQoL of newly diagnosed adults. Methods: Interviews were conducted with 13 adults (aged 40‐71; five males) with anaphylaxis (meeting WAO diagnostic criteria) to drugs, food, venom or spontaneous anaphylaxis, recruited using purposive sampling from allergy clinics in Birmingham, UK. Data were transcribed verbatim and analysed using thematic analysis. Results: Four themes were generated from the analysis: the journey from fear to frustration; the need to maintain a healthy identity; control over uncertainty; and the supportive role of others. Participants described their first experiences of anaphylaxis as frightening. Managing the condition was associated with frustration and anxiety, in part due to uncertainty regarding when anaphylaxis might occur. Participants did not consider their allergy as an illness and wanted to retain an identity as a healthy person. They felt a strong need to have control over their anaphylaxis so that it did not take over their lives. The support from others was extremely important, but a lack of understanding of anaphylaxis sometimes hindered that support. Conclusions and Clinical Relevance: Anaphylaxis has an adverse impact on the HRQoL of adults irrespective of the cause. More information about anaphylaxis and its management from healthcare professionals may help patients gain a sense of control over their condition and reduce the worry and anxiety associated with it.